Congenital cataract. Report 1. Modern concepts of etiology and principles of classification. A review of literature - N. Senchenko; K. Nagaeva; E. Ayuyeva; T. Iureva (Oftalʹmologiâ)
The analysis of literary sources, containing the results of research on the epidemiology and etiopathogenesis of congenital cataract, was made. The known classifications of this disease were also studied. The article describes the modern knowledge on the causal factors and pathogenic mechanisms, leading to irreversible pathological changes in the lens of the children. The evolution and effectiveness of clinical classifications was considered.